Collaboration and Context in the Design of Community-Engaged Research Training. Issue 3 (May 2021) - Ziegahn, Linda; Joosten, Yvonne; Nevarez, Lucinda; Hurd, Thelma; Evans, Jill; Dumbauld, Jill; Eder, Milton "Mickey"
Collaboration between academic researchers and community members, clinicians, and organizations is valued at all levels of the program development process in community-engaged health research (CEnR). This descriptive study examined a convenience sample of 30 projects addressing training in CEnR methods and strategies within the Clinical and Translational Science Awards (CTSA) consortium. Projects were selected from among posters presented at an annual community engagement conference over a 3-year period. Study goals were to learn more about how community participation in the design process affected selection of training topics, how distinct community settings influenced the selection of training formats, and the role of evaluation in preparing training participants to pursue future health research programming. Results indicated (1) a modest increase in training topics that reflected community health priorities as a result of community (as well as academic) participation at the program design stage, (2) a wide range of community-based settings for CEnR training programs, and (3) the majority of respondents conducted evaluations, which led in turn to revisions in the curricula for future training sessions. Practice and research implications are that the collaboration displayed by academic community teams around CEnR training should be traced to see if this participatory practice transfers to the design of health promotion programs. Second, collaborative training design tenets, community formats and settings, and evaluation strategies should be disseminated throughout the CTSA network and beyond. Third, common evaluative metrics and indicators of success for CEnR training programs should be identified across CTSA institutions.